HOW FREQUENTLY ARE PEOPLE WITH NEWLY DIAGNOSED PULMONARY TUBERCULOSIS DEFICIENT IN VITAMIN D LEVELS IN KHYBER PAKHTUNKHWA: A PILOT STUDY PROJECT - Mehr, Muhammad Tariq; Khan, Humera; Iman, Noor Ul (Journal of Postgraduate Medical Institute, 2016)
Objective: To estimate the frequency of vitamin D deficiency in patients with newly diagnosed pulmonary tuberculosis in Khyber Pukntunkhwa. Methodology: It was a descriptive cross sectional study conducted in a private consulting clinic at Ibrahimi Hospital, Dabgari Gardens, Peshawar from 01 April, 2014 to 30 June 2015. A total of 194 patients of either gender, between 15 to 70 years of age with newly diagnosed pulmonary tuberculosis were included in the study. 10cc of blood was obtained under strict aseptic technique and immediately sent to laboratory to estimate vitamin D levels. Results: Of the 194 patients included, 108(55.67%) were male and 86(44.33%) were females. Male to female ratio was 1.26:1. The frequency of vitamin D deficiency in patients suffering from pulmonary tuberculosis was observed in 82(42.27%) while 112(57.73%) were having normal vitamin D levels. More females 49(57%) were suffering from Vitamin D Deficiency compared to males 33(30.6%). Conclusion: Patients with pulmonary tuberculosis are significantly Vitamin D deficient. This deficiency was more marked in females.